PENGARUH PROJECT BASED LEARNING TERHADAP KEPUASAN MAHASISWA PADA MATA KULIAH PSI - Fitria Fitria; Emy Iryanie (Program Studi PGSD Universitas Flores, 2023)
Today, advances in learning media technology that previously consisted of audio and visual displays can be combined into multimedia forms. The aim of this study is to be a matter of consideration when choosing learning strategies through the evaluation of student learning experiences. This research is done by analyzing data using regression analysis. First, the data evaluation in this study is a data quality test. Next, do the classic assumption test. Third, a double linear regression analysis test is carried out to evaluate the accuracy and compatibility of the model. This is done to determine whether the regression model is worthy of knowing the free variable or not. The results of the study indicated that the variables of the PBL method in the learning process of the course have an influence on student satisfaction. A value of F of 117,321 and a significance of 0.000 indicate that the test result of F is < the defined significant rate (alpha = 0.05). Project-based learning methods applied in learning poses influence student satisfaction. So it can be concluded that the PBL learning model has an influence on student satisfaction in PSI courses.